Pemenuhan Hak – Hak Kesejahteraan Masyarakat Difabel di Provinsi Bali - Chrispayana, I Made Oscar Sakti; -, Bandiyah; Putra, I Ketut Erawan (Jurnal Nawala Politika, 2021)
The purpose of this research analyzes and describes how the fulfillment of rights that exist in the daily life of people with disabilities in Bali. The method used on this research is qualitative with an explanative descriptive type. The theory used on this research is Welfare State theory from Francis Fukuyama, Asa Briggs and Critical Theory from Iris Maroune Young. This theory explains state responsible  to make sure  the laws and policies that are born are obeyed by the citizen and also guarantee the rights and State should able to see another point of view from minorites how the public policy works. From the analysis carried out, there is a diversity of positions conveyed by the informants. Most of the informants revealed that the government or related institutions did not optimally implement a policy to make sure the rights for disabilities people. Keywords : Disabled Society, Welfare State, Critical Theory